Advancing researches on vegetable and fruit crops - Nath, Prem (Indian Horticulture, 2019)
The dynamic, forward looking and cohesive thinking with research aptitude of any research institute are pre-requisite for achieving sound research results. The contribution of intelligent and devoted research leader with team spirit provides necessary guidance with utilization of appropriate technologies to young and energetic researchers. The understanding of research mandate, areas of research and adoption of appropriate and advanced technologies are keys to ensuring the objectives of research goal. The vegetable breeding experience confirms that identifying objectives of breeding is prelude and key to successful results of a breeding programme in developing improved varieties. In order to identify the objectives, the views of the choice makers (state, consumer, grower, trader and researcher) which ensure the acceptance and popularity among farmers and consumers. The research areas listed illustrate the current issues related to vegetables and fruit and the research institution may prioritize them depending on the mandate and resources available. With the natural comparative advantage of raising more than two filial generations of vegetable crops in the field, the devoted and brilliant breeders and other researchers will continue to have tremendous opportunity to advancing researches at Hessaraghatta, the centre and heart of the IIHR, says Dr Prem Nath, a renowned horticulturist.